Two Reasoning Strategies in Patients With Psychological Illnesses - Gangemi, Amelia; Tenore, Katia; Mancini, Francesco (Frontiers in Psychology, 2019)
The hyper-emotion theory states that psychological disorders are conditions in which individuals experience emotions that are appropriate to the situation but inappropriate in their intensity. When these individuals experience such an emotion, they inevitably are compelled to reason about its cause. They therefore develop characteristic strategies of reasoning depending on the particular hyper-emotion they experience. In anxiety disorders (e.g., panic attack, social phobia), the perception of a threat leads to hyper anxiety, and the reasoning is corroboratory, adducing evidence that confirms the risk (corroboratory strategy). In obsessive-compulsive disorders, the perception of the threat of having acted in an irresponsible way leads to both hyper anxiety and guilt, and the reasoning is refutatory , adducing only evidence disconfirming the risk of being guilty (refutatory strategy). We report three empirical studies corroborating these hypotheses. They demostrate that patients themselves recognize the two strategies and spontaneously use them in therapeutic sessions and in evaluating scenarios in an experiment.